Packaging development in order to enhance image of Thai Traditional Herb Product and its standard suitable for China export / Ratanapat Suchat and Ohm Pattanachoti - Suchat, Ratanapat; Pattanachoti, Ohm (Faculty of Art and Design, 2019)
This project is conducted underneath the project titled Packaging Development in order to Enhance the Image of Thai Traditional Herb Product "Kwang Thong - Golden Deer Brand" and Its Standard Suitable for China and International Export which focuses on the concept of having a notably universal and good logo. This project has obtained a grant from the National Innovation Agency (public organization) (NIA). Therefore, in order to approach the packaging development, it has to follow the principles of design, studying examples of products in both Thai and Chinese market, analysing participant responses and conducting several testing stages until the final result presented that the objectives have been achieved. The finding also revealed that the satisfaction of overall packaging design was at the Good Level.